A Critical-analysis on the Development of Micro Grid in China. Issue 1 (March 2021) - Wang, Junhai; Yin, Jianbing; Chen, Lin; Chen, Zhiyuan; Gong, Yingfei; Tan, Qingkun
Abstract: With the combination of Internet, information technology and energy, micro grid plays an important role in the adjustment of energy structure with its abundant resources and friendly environmental benefits. This paper introduces the status of micro grid and renewable Energy of the status quo, In the second part, the development status of the micro-grid is introduced in the second part. In the third part, the future development trend of micro-grid is given. The conclusion of this paper and the suggestion of micro-grid development are given.